Number of replications and plot size for selection of maize progenies under "cerrado" and fertile soils - Resende, Marcos Deon Vilela de; Souza Júnior, Claudio Lopes de (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to obtain information on plot size and number of replicates necessary for evaluating progenies of corn (Zea mays L.) grown under cerrado and under fertile soils. Two hundred half-sib progenies of the BR 108 maize variety were used as experimental material. A method based on decreasing phenotypic variance and increasing genetic gain was applied. The increase in the number of replication was more efficient than the increase in plot size to obtain higher genetic gain; the increase in the number of replications led to similar response in genetic gain on both types of soils; the increase in the plot size led to higher response in genetic gain in the cerrado soil for ear weight. For ear weight, three replications with 20 plants per plot for the cerrado soil and three replications with 15 plants per plot for the fertile soil are indicated. For plant and ear height, three replications with three plants per plot for cerrado soil and three replications with five plants per plot for the fertile soil are indicated.